Rodent models of diabetic kidney disease: human translatability and preclinical validity. Issue 1 (January 2021) - Sembach, Frederikke E.; Østergaard, Mette V.; Vrang, Niels; Feldt-Rasmussen, Bo; Fosgerau, Keld; Jelsing, Jacob; Fink, Lisbeth N.
Highlights: Diabetic kidney disease (DKD) is a disease of high unmet therapeutic need. Several drugs are in clinical development for treatment of DKD. Rodent models of DKD show variable human translatability. Selection of a preclinical rodent model of DKD should be based on drug target. Rodent models of advanced DKD improve the ability to predict clinical outcomes. Abstract : Diabetic kidney disease (DKD) is the leading cause of end-stage renal disease (ESRD). Except for SGLT2 inhibitors and GLP-1R agonists, there have been few changes in DKD treatment over the past 25 years, when multifactorial intervention was introduced in patients with type 2 diabetes mellitus (T2DM). The unmet clinical need is partly due to the lack of animal models that replicate clinical features of human DKD, which has raised concern about the utility of these models in preclinical drug discovery. In this review, we performed a comprehensive analysis of rodent models of DKD to compare treatment efficacy from preclinical testing with outcome from clinical trials. We also investigated whether rodent models are predictive for clinical outcomes of therapeutic agents in human DKD.